Image Management of Rojanawit School Phitsanulok Province in the Situation of the Coronavirus 2019 - Kawwan, Butsakon; Chanvichai, Kittima (Journal of Buddhist Education and Research (JBER), 2025)
This qualitative study aimed to examine (1) the organizational image management process at Rojanawit Kindergarten in Phitsanulok Province, and (2) the tools and communication channels employed during the COVID-19 crisis. Data were collected through in-depth interviews with five key informants, including school administrators and staff. The findings revealed that the school adopted a comprehensive strategy to manage its public image during the pandemic. This included proactive planning, image promotion, protection, maintenance, and timely adjustments. Various communication methods - such as print materials, digital platforms, and activity-based media - were utilized to engage parents and the public while maintaining credibility. The school also developed adaptive approaches and problem-solving measures to strengthen trust and ensure the continuity of learning during the crisis.